Quality in early childhood services : an international perspective - Penn, Helen (McGraw-Hill, Open University Press, 2011)
"This book examines how quality and good practice in early childhood education and care (ECEC) is interpreted and implemented in a variety of settings and circumstances."-- Resumé vydavatele